Experimental Study on the Fractal Features and Permeability Characteristics of Low Metamorphic Coal Pore Structure under Thermal Damage - Zhen Liu; Mingrui Zhang; Shijian Yu; Lin Xin; Gang Wang; Liutao Sun (Geofluids)
Underground coal gasification and exploitation of geothermal mine resources can effectively improve coal conversion and utilization efficiency, and the basic theory of the above technologies generally relies on the change law of the coal pore structure under thermal damage. Therefore, the influence mechanism of the development of the coal pore structure under thermal damage is analyzed by the nuclear magnetic resonance experiment, and the temperature-permeability fractal model is created. The results show that compared with microtransitional pores, the volume of meso-macropores in the coal body is more susceptible to an increase in temperature, which was most obvious at 200-300°C. During the heating process, the measured fractal dimension based on the T2 spectral distribution is between 2 and 3, indicating that the fractal characteristics did not disappear upon a change in external temperature. The temperature has a certain negative correlation with DmNMR, DMNMR, and DNMR, indicating that the complexity of the pore structure of the coal body decreased gradually with the increase of the temperature. Compared with the permeability calculated based on the theoretical permeability fractal model, the permeability obtained from the temperature-permeability fractal model has a similar increasing trend as the permeability measured by the NMR experiment when the temperature increases. The experimental study on pore structure and permeability characteristics of the low metamorphic coal under thermal damage provides a scientific theory for underground coal gasification and geothermal exploitation.